2019
DOI: 10.1371/journal.pone.0216644
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and inequality of underweight and overweight among women of reproductive age: Evidence from the 2016 Nepal Demographic Health Survey

Abstract: Introduction Understanding socio-economic correlates and inequality of underweight and overweight is crucial to develop interventions to prevent adverse health outcomes. Materials and methods We analysed Nepal Demographic and Health Survey 2016 data from 6,069 women aged 15–49 years. WHO cut-offs for Body Mass Index categorised as: underweight (<18.5 kg/m 2 ), normal weight (18.5kg/m 2 to 24.9kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 55 publications
11
32
0
Order By: Relevance
“…Mothers who attended at least a secondary level of education had a higher risk of experiencing a double burden of malnutrition. This finding is supported by Rai et al, [33] who revealed that women who had primary/ secondary levels of education were more likely to be at risk of overweight/obesity. In contrast, various studies have also reported that the double burden of malnutrition is associated with a higher level of maternal education and wealth status [14,19,20].…”
Section: Discussionsupporting
confidence: 65%
“…Mothers who attended at least a secondary level of education had a higher risk of experiencing a double burden of malnutrition. This finding is supported by Rai et al, [33] who revealed that women who had primary/ secondary levels of education were more likely to be at risk of overweight/obesity. In contrast, various studies have also reported that the double burden of malnutrition is associated with a higher level of maternal education and wealth status [14,19,20].…”
Section: Discussionsupporting
confidence: 65%
“…Mothers who attended at least a secondary level of education had a higher risk of experiencing a double burden of malnutrition. This finding is supported by Rai et al, [36] who revealed that women who had primary/secondary levels of education were more likely to be at risk of overweight/obesity. In contrast, various studies have also reported that the double burden of malnutrition is associated with a higher level of maternal education and wealth status [16,21,22].…”
Section: Discussionsupporting
confidence: 65%
“…This study found that mothers from province number 2 were less likely to experience DBM compared with mothers from province 3. A possible reason could be that mothers from province number 2 are more likely to be of a lower socioeconomic status and consuming a less diverse diet with an estimated 29 % of minimum dietary diversity (MDD) [15] resulting in decreased likelihood of being overweight or obsese (11 %) [36,40]. According to the NDHS 2016 report, the prevalence of overweight/obesity was higher (35 %) in province number 3, as well as a higher consumption of diverse food groups with an estimated 64 % of MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of watching television was the main independent variable of this study, which was divided into the following three categories: (1) not watching television at all, (2) watching television less than once a week, and (3) watching television at least once a week [22]. The other covariates considered based on the literature review (which were found to be associated with overweight and obesity in previous studies) were age group [20], place of residence, province of residence [20], ecological region of residence [21], marital status [20], highest educational attainment [21], household wealth status [20], current employment status [24], parity [25], and number of household members in the family [26]. The categories of the covariates are mentioned in Table 1.…”
Section: Outcome Variables and Covariatesmentioning
confidence: 99%